The Impact of Financial Technology Small and Medium Enterprises : A Comparative Analysis - Putri, Walla Astianty; Jamalus, Jamalus; Rianto, Joko (Asosiasi Ide Bahasa Kepri, 2024)
The rapid evolution of Financial Technology (FinTech) has significantly reshaped the landscape of Small and Medium Enterprises (SMEs). This comparative study examines the impact of FinTech adoption on the growth, operational efficiency, and financial performance of SMEs across different sectors. By analyzing data from various industries, the study highlights the key areas where FinTech has accelerated business processes, enhanced financial inclusion, and increased access to funding. The research further explores challenges faced by SMEs in integrating FinTech solutions, including regulatory hurdles and technological readiness. The findings provide insights into the comparative advantages FinTech brings to SMEs in developed versus developing economies, suggesting policy recommendations to foster FinTech adoption and support SME growth. The results underscore the critical role of FinTech in transforming SMEs into more agile and competitive market players in the global economy.